Improvement of performance characteristics of repaired vehicle frames - Posviatenko, E. K.; Zabolotnyi, S. A.; Postupailo, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2015)
There has been suggested a method of reducing the heterogeneity structure of typical heat-affected zone areas through the use of heat-conducting plates, which allows improving the quality of repair of vehicle frames using welding processes.